Analyzing Predictive Factors for the Media’s Impact on the Nursing Profession - Jadranka Pavić; Marta Marković; Ana Marija Hošnjak; Aleksandar Racz; Irena Kovačević; Martina Smrekar (Nursing Reports)
Introduction: Mass media play a crucial role not only in informing the public but also in shaping public perception, educating, and enhancing the visibility of various professions, including nursing. Despite being the most populous healthcare profession, nursing remains underrepresented in media coverage. This imbalance affects the social status of the nursing profession and its public perception. Methods: This cross-sectional study utilized a validated questionnaire with high internal reliability (Cronbach’s alpha coefficients) to assess nurses’ perceptions of the media’s role in society and the nursing profession. Data were collected from 203 participants using an online survey employing the snowball sampling method. Statistical analyses included Welch ANOVA, t-tests, and hierarchical regression to predict the importance of media education. Results: Participants demonstrated positive perceptions of the media’s societal influence but identified a lack of adequate representation of nurses. Younger nurses and those with higher education levels emphasized the need for media education. Regression analysis revealed that perceptions of the media’s power and self-assessed media competencies were significant predictors of valuing media education. Conclusions: The findings highlight the need for integrating media literacy training into nursing education to enhance professional visibility and public engagement. This can empower nurses to actively contribute to shaping their professional image and addressing public misconceptions. Future research should expand the sample size and explore diverse healthcare settings to validate these findings.